Electron Paramagnetic Resonance Study of Cu2+ in Cd(HCOO)2·2H2O Single Crystal - Kalkan, H.; Köksal, F. (Elsevier Ltd, 1997)
The Electron Paramagnetic Resonance spectra of Cu2+ doped cadmium formate dihydrate single crystal and powder were investigated in the temperature range from 300 to 133 K. The observed values of the g and A hyperfine tensors were found to be temperature dependent and this dependence is discussed. The angular variation of the spectra indicated the substitution of the host Cd2+ with Cu2+. Two magnetically inequivalent sites for Cu2+ have been observed and the ground state wave functions of each site in the unit cell have been constructed. © 1997 Elsevier Science Ltd.
Keywords: D. Crystal and Ligand Fields; E. Electron Paramagnetic Resonance